Harmonization of Muslim and Christian Communities: A Study in Cermin Nan Gedang District - Wiwit Nopriani; Adi Iqbal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research departs from a unique phenomenon that occurs in the Muslim and Christian communities in Cermin Nan Gedang District. This study aims to explore and reveal the form of harmonization in the Muslim and Christian communities, the impacts, and factors that cause harmonization in Cermin Nan Gedang District. The research approach used by the researcher is field research, with a qualitative descriptive analysis research method. In this study, the researcher used observation, interview, and documentation methods as data collection instruments. The data analysis used data reduction, data presentation, and data verification. Meanwhile, the theory used to analyze this study is Nurcholis Madjid's theory on harmonization between Muslim and Christian communities. In this study, it was found that harmonization between the Muslim and Christian communities in Cermin Nan Gedang District is harmonious. The form of harmonization in establishing religious harmony in this district occurs at moments such as commemorating major holidays and traditional events such as weddings, from there they work together, mutual cooperation, and mutual assistance. This study concludes that the people of Cermin Nan Gedang District live side by side and as a community despite their different beliefs. This happens because they do not prioritize religion in social interactions, there is a process of brotherhood such as interfaith marriage and their awareness of the importance of harmonious unity between religious communities.